Ecofeminist Pragmatism of Female Founders in Sociology as Source of Women Empowerment in Academia and Society - Mušić, Lejla (International Journal of Emerging Trends in Social Sciences, 2017)
First female philosopher Hypathia and her tragic death is less known while as Minoan era of governing the island Crete represents the egalitarian society, in which females were equal as men, in profession, life and family. It is necessary to conduct the deconstruction and demystification of patriarchal approaches to society and education, in order to form contemporary sociological theory involving the female authors and their accomplishments. The eco feminist movement was founded during the radical and turbulent social changes of the early 1980s. The aftermath of war, global environmental movements and minority rights movements have joined forces to create significant subversion and an imitative position towards the patriarchal based theories. Major sociologist author and pragmatist, Nobel Prize Winner, who gained doctoral degree from Yale University and organized Hull House project for investigating the immigrant behaviour, influenced the eco feminist pragmatism of the Charlotte P. Gilman, and Caroline Bartlett Crane. This position is later on found in works of famous neo eco feminist and sociologists such as Ariell Salleh, Marija Geiger Zeman, Ivanka Buzov, and their ancestors, authors from different fields such as Val Plumwood, Karen J. Warren, Martha Kheel, Yenestra King, Françoise d’Eaubonne and Vandana Shiva. These authors have written about the ecological feminist movement, drawing attention to the need for scientific cognition of the way in which the logic of domination and oppression of women and nature is institutionalized. T is necessary to conduct the deconstruction and demystification of patriarchal approaches to society and education, in order to form contemporary sociological theory involving the female authors and their accomplishments.